Transcriptome analysis of the response to thyroid hormone in Xenopus neural stem and progenitor cells. Issue 2 (19th September 2022) - Cordero‐Véliz, Camila; Larraín, Juan; Faunes, Fernando
Abstract: Background: The thyroid hormones—thyroxine (T4) and 3, 5, 3′triiodothyronine (T3)—regulate the development of the central nervous system (CNS) in vertebrates by acting in different cell types. Although several T3 target genes have been identified in the brain, the changes in the transcriptome in response to T3 specifically in neural stem and progenitor cells (NSPCs) during the early steps of NSPCs activation and neurogenesis have not been studied in vivo. Here, we characterized the transcriptome of FACS‐sorted NSPCs in response to T3 during Xenopus laevis metamorphosis. Results: We identified 1252 upregulated and 726 downregulated genes after 16 hours of T3 exposure. Gene ontology and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis revealed that T3‐upregulated genes were significantly enriched in rRNA processing and maturation, protein folding, ribosome biogenesis, translation, mitochondrial function, and proteasome. These results suggest that NSPCs activation induced by T3 is characterized by an early proteome remodeling through the synthesis of the translation machinery and the degradation of proteins by the proteasome. Conclusion: This work provides new insights into the dynamics of activation of NPSCs in vivo in response to T3 during a critical period of neurogenesis in the metamorphosis. Key Findings: We characterized the transcriptome of Xenopus neural stem and progenitor cells (NSPCs) in response to 16 hours of T3 exposure. T3‐upregulated genes were significantly enriched in ribosome biogenesis, proteasome and mitochondrial function. Our results reveal new insights into the early dynamics of NSPCs activation during neurogenesis.